2018
DOI: 10.1186/s12885-018-4634-9
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of inflammatory breast cancer in Moroccan patients: clinical, molecular and pathological characteristics of 219 cases from the National Oncology Institute (INO)

Abstract: BackgroundUsually misdiagnosed, Inflammatory Breast Cancer (IBC) is the most aggressive form of non-metastatic breast cancer. This orphan disease is more frequent in North Africa. Despite intensive treatment, the survival rate remains very low.MethodsWe have retrospectively studied all breast cancer cases diagnosed at the National Oncology Institute (INO), Rabat between 2005 and 2010. We have collected 219 cases of women with metastatic and non-metastatic IBC. Data have been obtained from patients’ personal me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 32 publications
1
4
1
Order By: Relevance
“…Our findings with regard to hormone receptor expression, tumor histology, and presence of tumor emboli in the dermal lymphatics in IBC and non-IBC cases are similar to other studies (11)(12)(13)(14)19,22). Mammographic evidence of skin thickening and stromal coarsening/ thickened trabeculations among IBC cases was less common and axillary adenopathy (17,23) and a detected mass (17,20,23) were more common than reported in other studies.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our findings with regard to hormone receptor expression, tumor histology, and presence of tumor emboli in the dermal lymphatics in IBC and non-IBC cases are similar to other studies (11)(12)(13)(14)19,22). Mammographic evidence of skin thickening and stromal coarsening/ thickened trabeculations among IBC cases was less common and axillary adenopathy (17,23) and a detected mass (17,20,23) were more common than reported in other studies.…”
Section: Discussionsupporting
confidence: 89%
“…The prevalence of erythema, edema, and peau d'orange was generally higher and duration of these signs among IBC cases generally shorter in our study than in other studies in North Africa (10)(11)(12), which were based on medical record review (except for the Egyptian cases in reference 11). Notably, deficiencies in the information in medical records needed to identify IBC cases have been described (25).…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…The incidence of IBC varies considerably in different regions around the world. Studies have shown that IBC is more common in North Africa than in other parts of the world; the most recent estimates suggest that it represents 5% to 7% of all breast cancers in Tunisia [ 4 ], 4% to 5 % in Morocco [ 5 ], while in Egypt it has a rate of 11% [ 6 ]. IBC is also characterized by rapid progression and higher metastatic potential [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…This immunotherapeutic approach could be very attractive for IBC patients in North African countries; the IBC incidence ranges from ~5% to 11% of total breast cancers in Morocco, Algeria, Tunisia, and Egypt [ 22 , 56 , 57 , 58 ], making this specific disease a high economic burden for these countries. Hence, it is hard to disagree with Fahrer’s conclusion that “CFA therefore has the potential to be a simple and inexpensive form of cancer immunotherapy, accessible for use in both developed and emerging economies” [ 54 ].…”
Section: What Other Immunotherapies Could Be Applied With Isv To Ibc ...mentioning
confidence: 99%